Positron emission tomography (PET) imaging of neuroinflammation in healthy and Alzheimer disease participants using TSPO tracers - Fuh, Jong‐Ling; Lin, Yung‐Shuan; Yeh, Skye Hsin‐Hsien; Lee, Wei‐Ju; Chang, Wen‐Yi; Chang, Chi‐Wei; Yang, Bang‐Hung; Peng, Nan‐Jing; Huang, Wen‐Sheng (Alzheimer's & dementia, 2023)
Background Alzheimer’s disease (AD) is the most common type of dementia. In addition to the widely recognized accumulation of amyloid and tau protein being the core pathology of AD, neuroinflammation is another cause of brain dysfunction and structural change. Expression of translocator protein (TSPO) on the outer mitochondrial membrane of activated microglia is strongly associated with neuroinflammation. With the development of TSPO positron emission tomography (PET) tracer, we were able to evaluate neuroinflammation non‐invasively in a clinical cohort of AD spectrum. Method Cognitively impaired patients (including AD and mild cognitive impairment (MCI)) and cognitively normal controls (CN) were recruited from single dementia clinic. [18F]FEPPA, the second‐generation PET ligand specifically binds TSPO was synthesized fully automated. Structural brain MRI and functional PET imaging were performed simultaneously with a PET/MR scanner (SIGNA, GE Company, USA). Kinetic analyses were performed using PMOD 4.2 modeling software. Total distribution volume (VT) in each ROI, including frontal, temporal, inferiolateral parietal, occipital, hippocampus and cerebellum, were derived from a two‐tissue compartment model (2‐TCM). In addition, APOE and rs6971 polymorphism genotyping were conducted in all subjects. Mann‐Whitney U Tet, Kruskal‐Wallis Test and linear correlation were performed. Result A total of 39 participants (23 males and 16 females) participated, including 13 cognitively normal, 9 with MCI and 17 with Alzheimer’s disease. The rs6971 genotype had no significant effect on [18F]FEPPA binding to TSPO. The amount of TSPO expression was independent of age, gender, and APOE ε4 carrier status. The VT of each ROI did not differ significantly between cognitive groups. VT of frontal, temporal, inferiolateral parietal and occipital lobe were all negatively correlated with MMSE, Boston Naming Test and Trial Making A performance. However, such association was not observed between VT of hippocampus and cognitive tests. Conclusion Although there was no difference between TSPO expression in each ROI among cognitive groups, we still observed that higher TSPO expression in the cortex was associated with worse performance in certain cognitive tests. This implied that the increase in neuroinflammation was related to the decline of cognitive performance regardless of cognitive diagnosis.